Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2015)
This paper reviews recent developments in the financing of the Fund's concessional lending and debt relief since the October 2014 Update. It presents the latest available data including the new commitments of loan resources to the PRGT and the sources of initial financing for the newly created CCR Trust, replacing the PCDR Trust. It also discusses the PRGT's potential self sustaining capacity in the context of longer term projections of the demand for concessional lending and robustness to alternative scenarios.